2015
DOI: 10.1016/j.homp.2014.11.004
|View full text |Cite
|
Sign up to set email alerts
|

Homeopathic remedies with antineoplastic properties have immunomodulatory effects in experimental animals

Abstract: The results suggest immunomodulatory activity of homeopathic preparations in high dilution. This may be a mechanism through which homeopathic preparations act.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(16 citation statements)
references
References 23 publications
1
15
0
Order By: Relevance
“…Therefore, the protocol adopted was with Thuya occidentalis 30 cH, due to its proven action in reducing inflammatory responses in animals, involving reduction of edema, inhibiting the migration of neutrophils at the site of inflammation, reducing vascular permeability and pro-inflammatory cytokines, oxidative stress, in addition to an immunomodulatory effect [10]. In order to increase the speed of remission of fibropapillomas, the patient received HPV Biotherapic 30 cH as a association, maintaining the homeostasis of the organism, in an ideal process where the cure occurs through the reestablishment lasting health.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Therefore, the protocol adopted was with Thuya occidentalis 30 cH, due to its proven action in reducing inflammatory responses in animals, involving reduction of edema, inhibiting the migration of neutrophils at the site of inflammation, reducing vascular permeability and pro-inflammatory cytokines, oxidative stress, in addition to an immunomodulatory effect [10]. In order to increase the speed of remission of fibropapillomas, the patient received HPV Biotherapic 30 cH as a association, maintaining the homeostasis of the organism, in an ideal process where the cure occurs through the reestablishment lasting health.…”
Section: Discussionmentioning
confidence: 99%
“…That it may have a relationship of environmental change, showing that the prevalence of the disease is associated with water quality, pollution of coastal areas, areas with high human density, large contribution of agricultural, domestic, industrial and marine biotoxins, in such a way that the etiology of fibropapillomatosis can also serve to monitor the health of ecosystems [10,5,16]. A study with organic pollutant, polycyclic aromatic hydrocarbons, showed that turtles with FP had higher concentrations of this pollutant in the liver, than those that did not have FP [16].…”
Section: Case Reportmentioning
confidence: 99%
See 1 more Smart Citation
“…An animal model study (mice) showed immunomodulatory effects of homoeopathic medicines in high dilutions having antineoplastic effects thus proposing their mechanism of action through immune modulation [41] . Sabal serrulata, Conium maculatum and Thuja occidentalis showed no direct cellular anticancer effects in an experimental animal study but slow the progression of cancer and decrease cancer occurrence and mortality significantly in induced prostate cancer in rats.…”
Section: Mechanism Of Homoeopathic Medicines In Cancermentioning
confidence: 99%
“…Homeopathic Sabal serrulata significantly decreased the proliferation of human prostate cancer PC-3 cells and DU-145 cells and significantly decreased prostate tumor xenograft growth in mice [34]. Homeopathic Ruta, Hydrastis, Lycopodium, Thuja, Chelidonium, Natrum sulphuricum, Cholesterinum and Carcinosinum were found to exhibit immunomodulatory effects while inhibiting chemically induced carcinogenesis [35,36] and hepatotoxicity in rats and mice [37][38][39]. Homeopathic Condurango was found to modulate certain pro-and anti-apoptotic genes related to a caspase-3-mediated apoptotic pathway in benzopyrene-induced lung tumors in rats [40,41].…”
Section: Introductionmentioning
confidence: 99%